Pelatihan Penulisan Artikel Ilmiah bagi Dosen dan Mahasiswa STIT Pringsewu - Indah Wigati; Muhammad Toriq; Mohammad Syawaludin; Maryamah Maryamah (Jurnal SOLMA, 2026)
Background: Mastering scientific article writing skills is a crucial competency for lecturers and students, particularly to meet academic demands, publication requirements, and career development. However, many academics still face challenges in writing articles, such as topic selection, adapting to reputable journal formats, managing references, and even publication ethics. In response to these challenges, a Community Service activity was conducted in the form of scientific article writing training for lecturers and students at STIT Pringsewu. Methods: The event, held on July 20–21, 2025, involved 35 participants (15 lecturers and 20 students). The event featured interactive lectures, practical workshops, individual mentoring, and discussions and a Q&A session. The material covered scientific publication concepts, citation techniques, journal selection strategies, and publication ethics. Results: Evaluation results showed significant improvements in participant understanding, with 80% of lecturers and 70% of students achieving a high level of understanding. Furthermore, 12 participants successfully completed draft articles ready for revision, and an online mentoring group was formed for further guidance. Conclusions: Thus, this training effectively improves the scientific article writing competency of STIT Pringsewu academics and is recommended to be implemented continuously with a focus on the publication stage in nationally reputable journals.